CBIO-18. TP53-MUTANT OLIGODENDROGLIOMA: A SINGLE INSTITUTION CASE SERIES. (12th November 2021) - Webb, Mason; Kizilbash, Sani; Kollmeyer, Thomas; Jenkins, Robert; Sung, Sarah; Raghunathan, Aditya; Giannini, Caterina; Fung, Kar-Ming; Bouffard, John-Paul; Ida, Cristiane
Abstract: TP53 mutations are frequent in IDH-mutant astrocytomas but unusual in oligodendroglioma and the clinical significance of TP53 mutations in oligodendroglioma are not well characterized. We reviewed genetically defined oligodendroglioma (i.e., IDH-mutant, whole-arm 1p/19q-codeleted diffuse glioma) cases that were molecularly profiled (2017-2020) at our institution and identified 7 cases with TP53 mutation (9%; n=76). Molecular testing was performed using targeted neuro-oncology NGS panel (50-gene mutation and/or 187-gene mutation/rearrangement) and OncoScan™ microarray. Four (of 7) patients were female. Median age at diagnosis was 43 years (range, 23-63). Most common presenting symptom was seizures (3 of 7). All tumors were supratentorial. Histologically, 3 tumors were WHO grade II and 4 were WHO grade III. Two (of 3) patients with a WHO grade II tumor underwent biopsy and radiotherapy at diagnosis followed by temozolomide at recurrence (progression at 67 and 157 months after diagnosis; overall survival of 124 and 201 months). Three (of 4) patients with a WHO grade III tumor were diagnosed within the last two years and are currently progression-free after standard therapy. Molecularly, in addition to TP53 mutation(s), all cases had an IDH1 and TERT promoter mutation as well as other gene mutation(s) including FUBP1 (n=5), SETD2 (n=4), PIK3R1 (n=4), PIK3CA (n=3), NF1 (n=3) and CIC (n=3). In 3 (of 7) cases, the mutational profile with high mutation count enriched for C >T/G >A transitions was highly suggestive of a hypermutation phenotype (2 cases were recurrent tumors treated with temozolomide; a recurrent and a treatment-naïve tumor had mismatch repair gene mutation). Five (of 7) cases, including the 3 hypermutant cases, lacked functional TP53 (1 case with 2 mutations, 2 cases with 1 mutation plus loss of other copy, 2 cases with 1 mutation plus copy neutral loss-of-heterozygosity). TP53 mutations are uncommon in oligodendroglioma and appear enriched in hypermutant tumors.